The protective effect of melatonin on renal ischemia-reperfusion injury in the rat - YEGEN, BERRAK; ŞENER, GÖKSEL (BLACKWELL MUNKSGAARD, 2002)
Oxygen free radicals are considered to be important components involved in the pathophysiological tissue alterations observed during ischemia-reperfusion (I/R). In this study, we investigated the putative protective effects of melatonin treatment on renal I/R injury. Wistar albino rats were unilaterally nephrectomized and subjected to 45 min of renal pedicle occlusion followed by 1, 3, 6, 24, 48 hr or 1 wk of reperfusion. Melatonin (10 mg/kg, s.c.) or vehicle was administered twice, 15 min prior to ischemia and immediately before the reperfusion period. At the end of the reperfusion periods, rats were decapitated. Kidney samples were taken for histological examination or the determination of renal malondialdehyde (MIDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and protein oxidation (PO). Serum creatinine and blood urea nitrogen (BUN) concentrations were measured for the evaluation of renal function. The results revealed that I/R induced nephrotoxicity, as evidenced by increases in BUN and creatine levels at each time point, was reversed by melatonin treatment. The decrease in GSH and increases in MDA, MPO and PO induced by I/R indicated that renal injury involves free radical formation. As melatonin administration reversed these oxidant responses. improved renal function and microscopic damage, it seems likely that melatonin protects kidney tissue against oxidative damage.
Keywords: glutathione; ischemia; kidney; lipid peroxidation; myeloperoxidase; protein carbonilation; reperfusion; ANTIOXIDATIVE DEFENSE-MECHANISMS; INDUCED LIPID-PEROXIDATION; RADICAL SCAVENGER; NITRIC-OXIDE; IN-VITRO; FAILURE; KIDNEY; GLUTATHIONE; PREVENTION; MODEL